Method for preparing perovskite solar cell based on buried modification
By using the buried bottom modification method in perovskite solar cells, coating additives such as saccharin sodium and assembling perovskite absorbing layer and hole transport layer, the problems of perovskite battery in absorbing layer stability and interface recombination are solved. , significantly improves the photoelectric conversion efficiency and comprehensive performance of the battery.
Patent Information
- Application Number
- CN202411076909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
AI Technical Summary
Existing perovskite solar cells have shortcomings in improving the chemical stability of the absorbent layer and inhibiting interfacial carrier recombination, which affects their overall performance.
By using the buried base modification method, the perovskite film is suppressed by coating the surface of the electron transport layer of the perovskite solar cell with additives such as saccharin sodium, and assembling the perovskite absorbing layer, hole transport layer and back electrode on the surface of the substrate. ion migration and interface carrier recombination.
Improve the interface flatness of the electron transport layer, enhance the crystal quality of the perovskite film, inhibit the interfacial carrier recombination between the electron transport layer and the perovskite absorbing layer, release the interface residual stress, and enhance the perovskite battery. photoelectric conversion efficiency and comprehensive performance.
Smart Images

Figure CN119136613A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic photoelectric technology, and in particular relates to a method for preparing a perovskite solar cell based on buried modification. Background Art
[0002] As a new generation of photovoltaic clean energy technology, perovskite solar cells have received widespread attention from academia and industry. So far, the certified efficiency of perovskite cells has exceeded 26%, which is close to the highest efficiency of monocrystalline silicon solar cells. In order to seize the initiative in the photovoltaic industry, some manufacturing companies and venture capital are also pouring into the perovskite cell track. The structure of the perovskite cell is mainly composed of a conductive glass substrate, a carrier transport layer, a perovskite light absorption layer and a back electrode. Improving the chemical stability of the perovskite light absorption layer and inhibiting interface carrier recombination are important means to improve the comprehensive performance of perovskite cells. For formal perovskite cells, bottom modification is an effective method to improve the stability of the perovskite light absorption layer and inhibit interface carrier recombination. Summary of the invention
[0003] In view of the shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing a perovskite solar cell based on buried modification, which improves the comprehensive performance of the perovskite cell by inhibiting ion migration and interface carrier recombination of the perovskite film.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A method for preparing a perovskite solar cell based on buried modification, the method comprising the following steps:
[0006] (1) ultrasonically cleaning the ITO or FTO glass in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, and treating in a UV ozone cleaning machine for 10-30 minutes, and assembling an electron transport layer on the surface of the substrate by coating, evaporation or sputtering;
[0007] (2) dissolving the additive sodium o-benzoylsulfonyl imide (commonly known as sodium saccharin) in water to form a uniform solution with a concentration of 0.1-10 mg / ml, and coating it on the surface of the electron transport layer;
[0008] (3) Assembling the perovskite light absorbing layer, hole transport layer and back electrode in sequence on the substrate surface to obtain the desired perovskite solar cell.
[0009] Furthermore, the electron transport layer in step (1) is one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide or molybdenum oxide, or a composite thereof.
[0010] Furthermore, the saccharin sodium in step (2) can be replaced by acesulfame potassium (i.e., acesulfame potassium), aspartame (i.e., aspartame) or sodium cyclamate (i.e., sweetener) and mixtures thereof.
[0011] Furthermore, the water in step (2) can be replaced by a polar solvent such as an alkyl alcohol, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO).
[0012] Furthermore, the perovskite light-absorbing layer in step (3) includes but is not limited to any one of methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3) or methylamine tin bromide (MASnBr3) or their composites.
[0013] Furthermore, the hole transport layer in step (3) comprises poly(3-hexylthiophene) (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] The buried modification method used in the present invention is beneficial to improving the interface flatness of the electron transport layer, improving the crystal quality of the perovskite film, inhibiting the ion migration of the perovskite crystal and the interface carrier recombination between the electron transport layer and the perovskite light absorbing layer, helping to release the residual stress at the interface between the electron transport layer and the perovskite light absorbing layer, and ultimately improving the comprehensive performance of the perovskite battery, which is of great significance to the cost reduction and efficiency improvement of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A structural diagram of a perovskite battery prepared by the present invention;
[0017] Figure 2 This is a statistical chart of the photoelectric conversion efficiency of the perovskite cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0018] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0019] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0020] If the specific conditions are not specified in the embodiments of the present invention, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or obtained commercially. The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians of the art without making creative work are within the scope of protection of the present invention.
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] It should be noted that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.
[0023] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0024] Example 1
[0025] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and then annealed on a 150°C hot stage for 1 hour to obtain a SnO2 electron transport layer. 50μl of 0.5mg / ml sodium saccharin (sodium o-benzoylsulfonyl imide) aqueous solution was spin-coated on the substrate surface at a speed of 3000r / min for 30s to obtain a buried bottom modification layer. Then, equimolar amounts of MAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1.3mol / L, and the solution was spin-coated on the substrate surface. The speed of the gelator was set to 3000r / min. After drying for 25 seconds, 50μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin-coating at 3000r / min for 10 seconds, the ITO glass was placed on a 160°C hot stage and heated for 10 minutes to obtain a perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD in acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in an evaporator and an 80 nm gold film was evaporated as the back electrode. Figure 1 shown.
[0026] Example 2
[0027] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and annealed on a 180°C hot stage for 30 minutes to obtain a SnO2 electron transport layer. Take 50μl of 0.8mg / ml acesulfame potassium aqueous solution and spin-coat it on the substrate surface at a speed of 4000r / min for 25s to obtain a buried modification layer. Equimolar amounts of FAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1.5mol / L, and it was spin-coated on the substrate surface. Set the speed of the gelator to 3000r / min, spin dry for 15 seconds, drop 80μL of chlorobenzene on the center of the perovskite substrate, spin-coat at 3000r / min for 30 seconds, and then heat the ITO glass on a 160°C hot stage for 10 minutes to obtain a perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD in acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in an evaporator and a 70nm gold film was evaporated as the back electrode.
[0028] Example 3
[0029] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150°C hot stage for 40 minutes to obtain a SnO2 electron transport layer. 60 μl of 1 mg / ml aspartame aqueous solution was spin-coated on the substrate surface at a speed of 3500 r / min for 25 seconds to obtain a buried modification layer. FAPbI3 was dissolved in sulfolane to form a uniform solution with a concentration of 1.25 mol / L, and it was spin-coated on the substrate surface. The speed of the gelling machine was set to 3000 r / min, and after drying for 30 seconds, 80 μl of ethyl acetate was dropped on the center of the perovskite substrate. After spin coating at 3500 r / min for 20 seconds, the ITO glass was placed on a 150°C hot stage and heated for 15 minutes. The chlorobenzene solution of Spiro-OMeTAD in acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in a magnetron sputtering instrument and a 80nm silver film was vacuum sputtered as the back electrode.
[0030] Example 4
[0031] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and annealed on a 180℃ hot stage for 1 hour to obtain the SnO2 electron transport layer. 70μl of 2mg / ml sweetener aqueous solution was spin-coated on the substrate surface at a speed of 3500r / min for 25s to obtain the buried bottom modification layer. FAPbI3 was dissolved in a mixed solution of DMSO and DMF (the volume ratio of DMSO to DMF was 5:1) to form a uniform solution with a concentration of 1.0mol / L, and it was spin-coated on the substrate surface. The speed of the gelator was set to 3000r / min, and after drying for 30 seconds, 65μL of chlorobenzene solution was dropped on the center of the perovskite substrate. After spin-coating at 3500r / min for 20 seconds, the ITO glass was placed on a 150℃ hot stage and heated for 15 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD in acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in a magnetron sputtering instrument and a 80nm silver film was vacuum sputtered as the back electrode.
[0032] Example 5
[0033] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 10 minutes. The aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and annealed on a 180°C hot stage for 1.5 hours to obtain a SnO2 electron transport layer. 70 μl of a mixed aqueous solution of 3 mg / ml saccharin sodium and sweetener (the molar ratio of saccharin sodium to sweetener is 1:1) was taken and spin-coated on the substrate surface at a speed of 4500 r / min for 35 seconds to obtain a buried bottom modification layer. FAPbI3 and CsPbBr were dissolved in a mixed solvent of sulfolane and DMSO (the molar ratio of sulfolane to DMSO was 1:5) at a molar ratio of 19:1 to form a uniform solution with a total molar weight of 2.0 mol / L, and the solution was spin-coated on the substrate surface. The speed of the gelling machine was set to 3000 r / min. After drying for 15 seconds, 110 μL of 0.6 g / mL terephthaloyl chloride ethyl acetate solution was dropped on the center of the perovskite substrate. After 15 seconds of spin coating at 3000 r / min, the ITO glass was placed on a 170 ° C hot stage and heated for 10 minutes to obtain a perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI, was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in a magnetron sputtering instrument, and an 80 nm gold film was vacuum sputtered as the back electrode.
[0034] Comparative Example 1 (preparation without buried bottom layer)
[0035] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150℃ hot stage for 1 hour to obtain the SnO2 electron transport layer. Then, equimolar amounts of MAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1.3 mol / L, and it was spin-coated on the substrate surface. The speed of the gelling machine was set to 3000r / min. After drying for 25 seconds, 50μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000r / min for 10 seconds, the ITO glass was placed on a 160℃ hot stage and heated for 10 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI, was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in an evaporator and an 80nm gold film was evaporated as the back electrode.
[0036] The saccharin sodium can be replaced by acesulfame potassium (acesulfame K), aspartame (aspartame) or sodium cyclamate (sweetener) and mixtures thereof.
[0037] The water can be replaced by an alkyl alcohol, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) polar solvent.
[0038] The perovskite light-absorbing layer includes but is not limited to any one of methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3) or methylamine tin bromide (MASnBr3) or any one or a composite thereof.
[0039] The hole transport layer includes poly (3-hexylthiophene) (P3HT), 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (Spiro-OMeTAD).
[0040] Depend on Figure 2 It can be seen that the efficiency of the cells prepared in Examples 1-3 is significantly higher than that in Comparative Example 1. Therefore, the use of the bottom-burying modification method described in the present invention to prepare perovskite cells can improve the photoelectric conversion efficiency of the cells.
[0041] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application.
[0042] It will be appreciated that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.
Claims
1. A method for preparing a perovskite solar cell based on buried modification, It is characterized in that The method comprises the following steps: (1) ultrasonically cleaning the ITO or FTO glass in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, and treating in a UV ozone cleaning machine for 10-30 minutes, and assembling an electron transport layer on the surface of the substrate by coating, evaporation or sputtering; (2) dissolving the additive sodium saccharin in water to form a uniform solution with a concentration of 0.1-10 mg / ml, and coating the solution on the surface of the electron transport layer; (3) Assembling the perovskite light absorbing layer, hole transport layer and back electrode in sequence on the substrate surface to obtain the desired perovskite solar cell.
2. A method for preparing a perovskite solar cell based on buried modification according to claim 1, It is characterized in that The electron transport layer in step (1) is one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide or molybdenum oxide, or a composite thereof.
3. The method for preparing a perovskite solar cell based on buried modification according to claim 1, It is characterized in that The saccharin sodium in the step (2) can be replaced by acesulfame potassium, aspartame or sodium cyclohexanesulfamate and a mixture thereof.
4. The method for preparing a perovskite solar cell based on buried modification according to claim 1, It is characterized in that The water in step (2) can be replaced by a polar solvent such as alkyl alcohol, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO).
5. The method for preparing a perovskite solar cell based on buried modification according to claim 1, It is characterized in that The perovskite light absorbing layer in step (3) includes but is not limited to methylamine lead iodide (MAPbI 3 ), formamidinium lead iodide (FAPbI 3 ), methylamine lead bromide (MAPbBr 3 ), formamidinium lead bromide (FAPbBr 3 ), cesium lead iodide (CsPbI 3 ), cesium lead bromine (CsPbBr 3 ), methylamine tin iodide (MASnI 3 ) or methylaminetin bromide (MASnBr 3 ) or a complex thereof.
6. The method for preparing a perovskite solar cell based on buried modification according to claim 1, It is characterized in that The hole transport layer in step (3) comprises poly(3-hexylthiophene) (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
